Family Psychoeducation for Hepatitis C Patients and Their Families: Recommendation for Clinicians. Issue 3 (3rd July 2017) - Simpson, E. Whitney; Sims, Omar T.; North, Carol S.; Hong, Barry A.; Pollio, David E.
ABSTRACT: PsychoEducation Responsive to Families for Persons coping with Hepatitis C (HCV-PERF) is a multifamily psychoeducation group model designed to help patients with hepatitis C virus infection (HCV) and their families navigate the illness and improve their readiness for treatment. The purpose of this article is to provide information and recommendations for clinicians interested in using the HCV-PERF model. The article provides details of the intervention model and presents thematic categories that evolved from analysis of interviews with clinicians with experience conducting and facilitating HCV-PERF groups. Based on these findings, recommendations were developed to inform and guide the use of HCV-PERF.